HALOPHYTIC VEGETATION OF IRAN: TOWARDS A SYNTAXONOMICAL CLASSIFICATION - AKHANI, H. (Annali di Botanica, 2004)
Iran with its diverse c1irnatic conditions and geologic and land use history support large areas of saline habitats and diverse halophytic flora. The halophytic diversity in not only enriched by the evolving of a large number of autochthonous Irano-Turanian elements, but also many of the halophytes of other phytochoria like Saharo-Arabian, Mediterranean and even Euro-Siberian elements are represented in Iran. Therefore most of the higher syntaxa of Euro-Mediterranean and Afro-Asian-al last partly-occur in Iran. Prior to a consolidated syntaxonomical system for the halophytic vegetation of Iran, major halophytic vegetation units of Iran are summarized and shown along salinity and moisture gradients. These include: (I): Mangrove communities (Avicennio-Sonneratietea). (2): Submerged aquatic plant communities (Ruppietea maritimae). (3): Annual obligatory hygro-halophytic communities on sea, lake and river marshes dominated by stem or leaf succulent C3 chenopods (Thero-Salicornietea). (4) Semi-woody or perennial halophytic communities on muddy or coastal salt flats dominated by stem succulent C3 chenopods (Salicornietea fruticosae). (5): Hydrophi!ous euryhalophytic rush communities: Phragmitetea australis. (6): Halophytic grassland and herbaceous perennial sedge communities belonging to genera Puccinellia and Juncus (Juncetea maritimi). (7): Salt marsh and riverine bruchwood communities dominated by salt-excreting halophytes (Tamaricetea ramosissimae, prov.). (8): Annua1 halophytic communities dominated by C4 chenopods in temporary moist and inundated, or disturbed salty soils (Climacopteretea crassae, prov.). (9): Halophytic shrubby. semi-woody or hemicrytophytic communities on salty and dry soils dominated by lcaf or stem succulent C4 chenopods (Haloxylo-Salsoletea tomentosae, prov.). (1O): Halophytic shrub communities, on salty and sandy coastal or margin of sabkhas with high water table dominated by Nitraria schoberi and Reaumuria fruticosa. (11). Psarno-halophytic shrub communities along sandy coasts of Persian Gulf and Oman sea Sphaerocomion Bucheri and communities of Zygophyllum qatarense and Heliotropium bacciferum and (12): Unclassified halophytic communities: Herbaceous perennial and hemicryptophyte ha10phytic communities of secondary origin.